Evolution of the concept of disability during history: from medical to social model (Research, Society and Development, 2020)
This study aims to present the historical context of the concept of disability, following the history of humanity from ancient times on accounts of the process of inclusion and acceptance of people with disabilities to the present day. The content of the work is the result of a literature review on scientific articles, using terms of disability, psychology, deafness, historical context. The study's reflection presented a discussion in various areas of health on the topic addressed, but does not present a closed and concrete concept of what it is to be disabled, the Convention on the Rights of Persons with Disabilities mentions disability as “physical impediments, intellectual or sensory ”(UN, 2006, Article 1). In the face of human evolution and concepts of humanity, we leave the claim that people with disabilities are worthy of being excluded from society, to the idea of contemporary social inclusion, where support mechanisms and attention to these people are much larger, but still exist Many barriers. It is assumed that even so, unconsciously, we do not change such behaviors, but rather change into a social masking expressed through attitudes of pity and pity, such as dealing with these individuals denying their self-sufficiency.